Celiac Disease as a Cause of Anemia and Brittle Diabetes in Type 1 Diabetes Mellitus - Thewjitcharoen, Yotsapon; Viriyautsahakul, Vichai; Sasijaroenrat, Natthaporn; Komindr, Surat; Chotwanvirat, Phawinpon; Nongkhunsarn, Chadaporn; Nakasatien, Soontaree; Himathongkam, Thep (Journal of the ASEAN Federation of Endocrine Societies, 2022)
Untreated celiac disease (CD) leads to an increased risk for hypoglycemia and diabetic complications. However, the diagnosis of CD can be challenging and some extra-gastrointestinal tract manifestations could be a presenting symptom. We report a case of a 29-year-old Indian male with brittle T1DM whose underlying CD was discovered from a work-up for anemia. After an introduction of a gluten-free diet, he gained 5 kgs in two months, was responsive to oral iron supplement, and had stable glycemic control with much less hypoglycemia. Even though this disease is rare in Asian populations, the diagnosis of celiac disease should always be kept in mind when people with T1DM present with unexplained microcytic anemia and/or unexplained hypoglycemia.